Aqueous foams stabilized with silica nanoparticle and alpha olefin sulfonates surfactant - T. A. T. Mohd; N. F. Abu Bakar; N. Awang; A. A. Talib (Journal of Mechanical Engineering and Sciences, 2018)
Carbon dioxide (CO2) foams have been introduced to improve mobility of CO2 in CO2 flooding. However, using surfactant alone to stabilize CO2 foam has potential weaknesses such as high surfactant retention in porous media and the foam is thermodynamically unstable for a long-term. Nanoparticle has been an alternative in stabilizing CO2 foam longer. This study aims to analyze CO2 foam stability at varying concentrations of surfactant, silica nanoparticle (SNP) and brine. The additions of SNP in anionic surfactant of alpha olefin sulfonates (AOS)-water and in AOS-brine towards foam stability were demonstrated in this study. CO2 foam stability was measured through the foam height observation and bubble size analysis. The performance of SNP and AOS suspensions in stabilizing foam were observed at different concentrations of AOS (0.1, 0.3 and 0.5 wt%), SNP (0.1, 0.3 and 0.5 wt%) and brine (0.1, 1 and 5 wt%). The results revealed that the CO2foams were most stable at 0.3 wt% SNP suspension in 0.5 wt% AOS-water. It was found that the most stable foams formed at concentration of 1 wt% of brine. Smaller and uniform bubble size has been produced at 0.3 wt% SNP in 0.5 wt% AOS solution. Thus, concentrations of surfactant, SNP and brine have significant effects on CO2 foam stability.